Success stories of Malaysia's global reach and CLMV Programme - Abdul Rahman, Shukran (IIUM Press & Institut Penyelidikan Pendidikan Tinggi Negara (IPPTN), 2018)
This book consists of 6 chapters which have been authored by those involved in the Malaysia’s Global Reach or Jangkauan Global Malaysia (JGM) and Cambodia, Lao PDR, Myanmar and Vietnam (CLMV) projects. The book is the concerted efforts of all private and public Higher Learning Institutions whose focus is to nurture the soft approaches in the region. The articles published in this book feature the implementation and outcomes of the projects which have contributed significantly to social economic development, especially in the areas of education, cultural development, environmental development, health and technology. Though it is stated that the targeted readers for this book are academicians and who involve in the education field but I personally think this book can be read, and adapted by other segments of society especially amongst those who have interests in community engagements. The language used is easy to understand with little technical terms. This book is interesting as it has not only showcased some of the major projects carried out by the Malaysian Government through its Global Reach programme and CLMV programmes such as in MyExpert Cluster and MySkill Cluster but it also narrated and demonstrated the significant outcomes and valuable input for other readers who intend to commence, adopt and adapt the similar initiatives in different setting.